Wikis: Developing pre-service teachers' leadership skills and knowledge of content standards - Angelia Reid-Griffin; Kelli M. Slaten (Lectito Journals, 2016)
In this initial phase of our multi-year research study we set out to explore the development of leadership skills in our pre-service secondary teachers after using an online wiki, Wikispaces. This paper presents our methods for preparing a group of 13 mathematics and 3 science secondary pre-service teachers to demonstrate the essential knowledge, skills and dispositions of beginning teacher leaders. Our findings indicate the pre-service teachers' overall satisfaction with demonstrating leadership through collaborative practices. They were successful in these new roles as teacher/collaborator within the context of communication about content standards. Though the candidates participated in other collaborative tasks, this effort was noted for bringing together technology, content standards and leadership qualities that are critical for beginning teachers. Implications for addressing the preservice teachers' development of leadership skills, as they become professional teachers will be shared.